1995
DOI: 10.1038/bjc.1995.288
|View full text |Cite
|
Sign up to set email alerts
|

TP53 gene mutations and protein accumulation in primary vaginal carcinomas

Abstract: Summary Primary carcinomas from 46 patients were screened for TP53 alterations. Immunohistochemistry demonstrated nuclear TPS3 protein accumulation in 22 (48%) cases using the polyclonal CM1 antiserum, whereas 15 (33%) cases showed positive nuclear staining with the mononuclear antibody PAb 1801. Constant denaturant gel electrophoresis (CDGE) was used to screen 27 of the vaginal carcinomas for mutations in the conserved regions of the TP53 gene (exons 5-8 (Lane and Benchimol, 1990). Although the precise mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…However, no significant association between TP53 alteration and survival has so far been observed in PCV. 11,13 In the present study, in agreement with previous reports, we found that most of PCV patients had no overexpression of p53 (81%). However, we noticed that overexpression of p53 was significantly associated with short-term survival.…”
Section: P53 and P21supporting
confidence: 95%
See 1 more Smart Citation
“…However, no significant association between TP53 alteration and survival has so far been observed in PCV. 11,13 In the present study, in agreement with previous reports, we found that most of PCV patients had no overexpression of p53 (81%). However, we noticed that overexpression of p53 was significantly associated with short-term survival.…”
Section: P53 and P21supporting
confidence: 95%
“…11,13,30,37 In the study by Habermann et al, 30 low expression of p53 was detected in 14 of 16 PCV together with high expression of p21 (WAF-1). Skomedal et al 13 investigated 46 PCV and found that 50% had a TP53 gene mutation and/or protein accumulation, with a 70% correlation between mutation and immunohistochemical data.…”
Section: P53 and P21mentioning
confidence: 93%
“…In the present study there were no significant correlations between p53 protein accumulation and sex, age, tumour stage at diagnosis, histopathological tumour grading or prognosis. This is in accordance with previous studies that failed to find prognostic significance of p53 in carci nomas of the ovary [ 18], uterine cervix [ 19], vagina [20], colon [21] and head and neck [22], In contrast, other stud ies have demonstrated a relationship between p53 abnor malities and aggressive behaviour of breast [23], uterine [24] and gastric [25] carcinomas. It is uncertain if these differences represent true biological effects of p53 or if they only reflect methodological errors.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have revealed varying degrees of discordancy. 31,32 Six cases with eight mutations in the TP53 gene did not show positive immunostaining. Mutations -+ *Four semi-quantitative classes were used to describe the number of immunostained tumour cells: , none; +, less than 5 per cent of the cells; + +, 5-50 per cent of the cells; and + + +, more than 50 per cent of the cells.…”
Section: Discussionmentioning
confidence: 89%